Radio(chemo)therapy with curative intent for anal cancer – effectiveness and toxicity in elderly vs. younger patients - Anczykowski, Mahalia Zoe; Rösel, Polina; Ziegler, David Alexander; Fischer, Laura Anna; Guhlich, Manuel; El Shafie, Rami A.; Rieken, Stefan; Dröge, Leif Hendrik; Leu, Martin (Frontiers in Oncology, 2025)
BackgroundPrimary radio(chemo)therapy is a therapeutic standard strategy for advanced anal squamous cell carcinoma (ASCC). For elderly patients evidence concerning long-term oncological outcome is scarce.Methods160 patients with advanced ASCC treated primarily by radio(chemo)therapy with curative intent were included. Baseline characteristics such as the Charlson Comorbidity Index as well as treatment-associated and long-term oncologic outcomes of patients with advanced (≥ 70 years) and younger (< 70 years) age were compared.ResultsElderly patients had more comorbidities. They less frequently received concomitant chemotherapy. Acute enteritis ≥ III° and late pelvic bone fracture occurred more frequently in elderly patients. Overall survival and progression-free survival estimates were significantly lower for elderly patients, respectively (OS: HR 2.53, 95% CI 1.54-4.18; p < 0.001 and PFS: HR 2.10, 95% CI 1.29-3.42; p = 0.003). Locoregional and distant control did not show significant differences between elderly vs. younger patients.ConclusionPrimary radio(chemo)therapy seems to be an effective and relatively safe treatment option also in elderly patients. The lower overall and progression-free survival estimates as well as the negative survival influence of a higher comorbidity index strengthen the necessity to comprehensively weighing up and discuss potential benefits and side effects of primary radio(chemo)therapy.